Investigation of EMS effect on Vicia faba seed germination and seedling growth under saline condition - Elmeer, Khaled; Abduljawad, Eman; Eljrary, Ebtisam (Al-Mukhtar Journal of Sciences, 2016)
The effect of Ethyl-methane Sulphonate (EMS) on seed germination and seedling characters of broad beans (Vicia faba L.) was analyzed in this investigation. The seeds were soaked in different percentages and durations of (EMS), then after sowing were irrigated with a range of NaCl concentration. The effect of EMS was observed based on the seed germination (%), and seedling characters such as: total fresh weight, root fresh weight and root length. Germination percentage generally decreases while concentrations of NaCl increases, however the interaction effect of EMS clearly appeared on concentration 6000 ppm NaCl, which positively increased the germination from 40% in absence of EMS to 60%, when 0.5 or 1% EMS were used. 24 hours soaking in EMS decreased the fresh weight from 33.36 to 13.55 gm per plant, in addition to the decrease of the root length from 22.0cm to 14.2cm per plant. The root nodulation of broad bean is not affected during the increase of NaCl, possibly due to the interactional effect of mutagenesis agent.